PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ROOF TOP PADA GEDUNG GUDANG UTAMA PT PEMBANGKIT JAWA BALI UNIT MUARA KARANG - Muhammad Aditya Salim; Insani Abdi Bangsa (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
It should be noted that electricity demand in Indonesia reached 1,109 kWh per capita in the third quarter 2021 that figure is equivalent to 92.2% of the target in 2021 of 1,203 kWh per capita electricity consumption per capita has continued to increase since 2015 and the highest increase occurred in 2017 of 6.80% while the lowest increase occurred in 2020 of 0.4%. On-grid PLTS are solar panels and inverters. Meanwhile, off-grid PLTS works continuously independent without being connected to the PLN network. The method used in the research This is the observation method. The observation method is a data collection technique that is carried out through an observation, accompanied by notes on the situation or the behavior of the target object. The application of rooftop PV mini-grid construction in PV mini-grid projects rooftop at PT. Muara Karang PJB unit uses an on-grid system which means the PLTS system will only generate electricity when there is electricity from the grid (PLN). generated from a rooftop solar power plant (PLTS) in the main warehouse building of PT. PJB estuary unit based on the calculations carried out is 669.8496 kWh / day. Power that produced will change with the intensity of sunlight in the area, where if low intensity the power generated will be low and if the intensity is high the power generated will be high. Perlu diketahui kebutuhan listrik di Indonesia mencapai 1.109 kWh per kapita pada kuarta III 2021 angka itu setara dengan 92,2% dari yang di targetkan pada tahun 2021 sebesar 1.203 kWh per kapita kosumsi listrik per kapita terus meningkat sejak 2015 dan peningkatan tertinggi tejadi pada tahun 2017 sebesar 6,80% sedangkan peningkatan terendah terjadi pada tahun 2020 sebesar 0,4%. PLTS on-grid adalah panel surya dan inverter. Sedangkan PLTS off-grid bekerja secara independen tanpa dihubungkan dengan ke jaringan PLN. Metode yang digunakan dalam penelitian ini adalah metode observasi.Metode observasi adalah teknik pengumpulan data yang dilakukaan melalui sesuatu pengamatan, dengan disertai pencatatan-pencatatan terhadap keadaan atau prilaku objek sasaran.Penerapan pembangunan PLTS rooftop pada proyek pembangunan PLTS rooftop di PT. Unit PJB muara karang menggunakan sistem on-grid dimana berarti sistem PLTS hanya akan menghasilkan listrik ketika terdapat listrik dari jaringan (PLN).Daya maksimal yang dihasilkan dari pembangkit listrik tenaga surya (PLTS) rooftop di Gedung Gudang utama PT. PJB unit muara karang bedasarkan perhituang yang dilakukan adalah 669,8496 kWh / hari. Daya yang dihassilkan akan berubah seiring intensitas cahaya matahari di daerah tersebut, di mana bila intensitas rendah daya yang dihasilkan akan rendah dan jika intensitas tinggi daya yang dihasilkan akan tinggi.